A 235 Kb deletion at 17q21.33 encompassing the COL1A1, and two additional secondary copy number variants in an infant with type I osteogenesis imperfecta: A rare case report. Issue 6 (13th April 2020) - Numbere, Numbereye; Weber, David R.; Porter, George; Iqbal, Mohammed A.
Abstract: Background: Osteogenesis imperfecta (OI) is a rare group of disorders characterized by increased susceptibility to fractures due to genetically determined bone fragility. About 90% of cases are due to mutations in COL1A1 (17q21.33) or COL1A2 (7q21.3) resulting in quantitative or qualitative defects in type I collagen, a key structural constituent of bone. OI due to complete COL1A1 deletion is rare. Methods: We present a case of OI type I in a Caucasian female referred at 10 months of age for investigation of multiple fractures associated with minimal or no known trauma, small stature, and blue sclera. Her father has four to five lifetime fractures, blue sclera, normal stature, and a 14.5 kilobase (kb) deletion of COL1A1 detected by targeted array performed at an outside institution. Microarray comparative genomic hybridization was performed on the proband and all members of the family. Results: A previously unreported 235 kb deletion at 17q21.33 encompassing COL1A1, ITGA3, PDK2, SGCA, and HILS1 was detected in the proband. Also identified in both the proband and sibling is a maternally inherited 283 kb gain at 8p21.3 encompassing CSGALNACT1 and a 163 kb loss at 10q21.3 encompassing CTNNA3 . Analysis in the father revealed the same size deletion at 17q21.33 as in the proband. Conclusion: Together with previously reported cases of COL1A1 deletions, this case report emphasizes the importance of a whole‐genome DNA copy number assessment in patients suspected for OI, which will elucidate the presence of precise COL1A1 deletions and any pathogenic secondary copy number variations. Abstract : Whole‐genome DNA copy number assessment in patients suspected for OI will elucidate the presence of precise COLIA1 deletions and any secondary pathogenic copy number variations. This case report highlights the importance of large COLIA1 deletions and secondary copy number variations in identifying clinical features which may establish as yet unknown variants of OI and lead to improved management and genetic counseling of patients.